Projeto de vida e o mundo do trabalho: desafios e possibilidades no contexto do ensino médio - Carvalho, Vera Lucia Gonçalves (2024)
Relations with the world of work are especially complex, as they involve economic, social, cultural and educational aspects that directly impact life in society, especially young people in high school. It is important that young people reflect on these issues both inside and outside of school, recognizing that they live in contexts and experiences that, at the same time, distinguish and connect them. They occupy different roles in society and education plays a central role in their formation. This evident complexity is manifested, in part, by the constant evolution of demands in the world of work, driven by technological, economic and social changes in the globalized world. During high school, young people begin to explore paths already facing the challenges of this changing reality. For the study of this dissertation, our general objective is to understand possibilities and challenges in the development of Life Projects with young people in high school, considering contexts of precariousness and flexibility in the world of work. The research methodology adopted is a qualitative, bibliographical approach with documentary analysis. The main guiding question of the investigation is: What are the possibilities and challenges in developing Life Projects with young people in high school, considering contexts of precariousness and flexibility in the world of work? We aim to understand historical milestones of transformations in the world of work and their effects of precariousness and flexibility; discuss how the world of work relates to education, particularly high school, in order to establish personal and social implications for young people's life projects. Anchoring ourselves in pertinent theoretical foundations and authors such as Ricardo Antunes (2002, 2005, 2015, 2017, 2020), Richard Sennett (2009), Anthony Giddens (1990) and Dardot and Laval (2016). To conclude, it was highlighted that it was important to debate the limits and potential of the curricular component "Projeto de Vida e Mundo do Trabalho" in the context of high school youth in the municipality of Concórdia/SC. The research showed that the documents that guide the Teachers of the Component, such as the Base Curriculum of the Catarinense Territory and the Pedagogical Guides of the Life Project Component, from the state network, focusing on the Coordination of Concordia/SC, provide support for the pedagogical practice of teachers in a partial way so that students reflect on their life projects, highlighting some limits for working with the component.